Impact of Mannose-Binding Lectin Deficiency on Radiocontrast-Induced Renal Dysfunction. (10th December 2013) - Osthoff, Michael; Trendelenburg, Marten
Abstract : Contrast-induced nephropathy (CIN) is the third leading cause of acute renal failure in hospitalized patients. Endothelial dysfunction, renal medullary ischemia, and tubular toxicity are regarded as the most important factors in the pathogenesis of CIN. Mannose-binding lectin (MBL), a pattern recognition protein of the lectin pathway of complement, has been found to aggravate and mediate tissue damage during experimental renal ischemia/reperfusion (I/R) injury which was alleviated by inhibition with C1 inhibitor, a potent MBL, and lectin pathway inhibitor. In this paper, we highlight the potential role of MBL in the pathogenesis of human CIN. In experimental I/R models, MBL was previously found to induce tubular cell death independent of the complement system. In addition, after binding to vascular endothelial cells, MBL and its associated serine proteases were able to trigger a proinflammatory reaction and contribute to endothelial dysfunction. In humans, urinary MBL was increased after administration of contrast media and in individuals with CIN. Moreover, individuals with normal/high MBL levels were at increased risk to develop radiocontrast-induced renal dysfunction. Hence, MBL and the lectin pathway seem to be a promising target given that a licensed, powerful, human recombinant inhibitor exits to be added to the scarce armamentarium currently available for prophylaxis of CIN.